2020
DOI: 10.3390/ijerph17093257
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness, Body Composition, and Adherence to the Mediterranean Diet in Young Football Players: Influence of the 20 mSRT Score and Maturational Stage

Abstract: This study aimed to analyze the differences in physical fitness variables, body composition, and adherence to the Mediterranean diet according to the cardiorespiratory fitness and the maturational stage in young football players. A total of 194 male football players (aged 8–16) from three football sport schools participated in this study. Data on cardiorespiratory fitness (the 20-m shuttle run test), anthropometric measurements, handgrip strength, respiratory capacity (forced spirometry), and adherence to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, and despite the fact that in our sample the predominant levels of adherence were good and medium, no significant differences were found in the distribution of the level of MD adherence. Manzano-Carrasco et al (2020b) , after evaluating young soccer players, also found no significant differences in the KIDMED questionnaire score. This could be due to the fact that the MD is being substituted by foods characteristic of other cultures, mainly affecting adolescents ( Rubio-Árias et al, 2015 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, and despite the fact that in our sample the predominant levels of adherence were good and medium, no significant differences were found in the distribution of the level of MD adherence. Manzano-Carrasco et al (2020b) , after evaluating young soccer players, also found no significant differences in the KIDMED questionnaire score. This could be due to the fact that the MD is being substituted by foods characteristic of other cultures, mainly affecting adolescents ( Rubio-Árias et al, 2015 ).…”
Section: Discussionmentioning
confidence: 76%
“…However, very few studies have analyzed adherence to the MD in young athletes, and how it influences sports performance, body composition characteristics, or both, not finding a high adherence of young athletes to this dietary pattern. ( Rubio-Árias et al, 2015 ; Vaquero-Cristóbal et al, 2018 ; Manzano-Carrasco et al, 2020b ; Martínez-Rodríguez et al, 2021 ). In addition, no studies have been found about handball players.…”
Section: Introductionmentioning
confidence: 98%
“…Besides, girls showed a higher percentage of body fat mass compared to boys, which may also be due to a higher level of a sedentary lifestyle and, therefore, the lesser practice of physical activity of the girls, which are determining factors of NCDs [ 53 ]. Conversely, the boys showed a higher percentage of lean body mass, which gives them a higher ability to achieve greater levels of cardiorespiratory fitness and strength [ 54 ]. Thus, in childhood as well as adolescence it is essential to acquire a balanced diet that may contribute to optimal health, growth and cognitive development.…”
Section: Discussionmentioning
confidence: 99%
“…Weight (kg); body fat (%); body mass (kg) and skeletal muscle mass (%); fat mass in the upper body and lower body (%); and muscle mass in (kg) were measured by a portable segmental multifrequency body composition analyser (Tanita MC-780; Tanita Corporation, Tokyo, Japan). The body mass index (BMI) was calculated with the weight (kg) divided by the squared height of the girls [29]. Participants completed this test after an overnight fast without any intensive exercise on the day before [30].…”
Section: Body Compositionmentioning
confidence: 99%
“…The forced vital capacity (FVC)-which is the volume delivered during an expiration made as forcefully and completely as possible, starting from a full inspiration-and the forced expiratory volume in one second (FEV)-which is the volume delivered in the first second of an FVC manoeuvre-were recorded [32]. The best result of two attempts was used for the analysis [29].…”
Section: Spirometrymentioning
confidence: 99%